Aumento das cargas de trabalho em técnicos de enfermagem na atenção primária à saúde no Brasil - SCHERER, Magda Duarte dos Anjos (Universidade Federal do Pará, 2018)
In this article we analyze the main aspects that contribute to increase the workloads of nurse technicians working in primary health care in Brazil, we identify the type of loads and rank the most prevalent aspects of this occupational group. It is based on a multicenter study with 24 professionals from the South, Center-west and North regions of Brazil, from 2011 to 2013, using data from semi-structured interviews. The data were systematized in Atlas.ti software and submitted to thematic analysis. The aspects that contribute to increasing workloads are low monthly remuneration, lack of material resources, work overload, wear and illness, relationship with the user, and lack of human resources, prevailing psychological and physiological loads. Adequacy of the conditions and organization of work are shown paramount to ease the workload on the primary health care setting, and to promote the health, wellbeing and quality of life in the nurse technicians working environment.